2022
DOI: 10.1140/epjc/s10052-022-10268-2
|View full text |Cite
|
Sign up to set email alerts
|

Realistic neutron star models in f(T) gravity

Abstract: We investigate the nonrotating neutron stars in f(T) gravity with $$f(T)=T+\alpha {T}^2$$ f ( T ) = T + α T 2 , where T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…More importantly, the hard segment of HPD is cyclohexane, which is relatively flexible compared to the aromatic benzene of XPD. Using a Fourier‐transform infrared spectroscopy (FT‐IR), it is previously reported that the steric hindrance of the cyclohexane ring in H 6 XDI interrupts the formation of hydrogen bonds between the urethane group and polymer chains, [ 37 ] while the aromatic benzene ring structure of XDI allowed the formation of additional hydrogen bonds. This is manifested by ≈8 times longer recovery time of 0.15 XPD (142 s) compared to that of 0.15 HPD (18 s).…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, the hard segment of HPD is cyclohexane, which is relatively flexible compared to the aromatic benzene of XPD. Using a Fourier‐transform infrared spectroscopy (FT‐IR), it is previously reported that the steric hindrance of the cyclohexane ring in H 6 XDI interrupts the formation of hydrogen bonds between the urethane group and polymer chains, [ 37 ] while the aromatic benzene ring structure of XDI allowed the formation of additional hydrogen bonds. This is manifested by ≈8 times longer recovery time of 0.15 XPD (142 s) compared to that of 0.15 HPD (18 s).…”
Section: Resultsmentioning
confidence: 99%
“…(7) Our intention is to construct a model of static compact objects, hence, considering a static and spherically symmetric line element ds 2 = γ 2 00 dt 2 − γ 2 11 dr 2 − r 2 dθ 2 − r 2 sin 2 θdϕ 2 . Thus, the vierbein or tetrad in the Schwarzschild coordinate systems is given by [29] (8) The tetrad in Eq. ( 8) is non-diagonal, but it is considered a "good tetrad" (see Ref.…”
Section: Modified Teleparallel Gravity and Field Equationsmentioning
confidence: 99%
“…Sometimes these theories may fail in solar system scales, but in several cases, they are still useful in the context of effective theories. Applications of modified theories of gravity have been discussed on several areas like compact objects, early universe, gravitational waves and so on [8,23,24,[26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The study of the neutron star is also a hot topic in literature. In f (T ) gravity, the contribution about the inspection of neutron star with the aid of model f (T ) = T (1 + αT ) is carried out by Lin et al [21]. They found that in the case of a negative value of α, the large size of the matter is held by the neutron star.…”
Section: Introductionmentioning
confidence: 99%